2016
DOI: 10.1200/jco.2016.34.2_suppl.83
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of an online surgeon scorecard by the general public and its effect on adults changing cancer surgeons even when presented with complication rates that are statistically equivalent.

Abstract: 83 Background: Recently Pro-Publica, an independent, non-profit newsroom, created a surgeon scorecard. This scorecard reports calculated death and complication rates for surgeons performing elective procedures in Medicare patients, including radical prostatectomy. We wanted to understand how the general population would interpret these data and whether it would influence surgeon choice. Methods: 265 adults at the Minnesota State Fair were recruited to participate in a survey requiring interpretation of a repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Work by other groups highlights the potential unintended consequences of presenting information in a way that is not understandable. For example, a recent survey of adults presented with cancer surgery outcome data displayed in a fashion typical of outcome reports (designed without patient input) demonstrated that almost half of those surveyed said they would switch surgeons, when the data did not in fact show any clinically or statistically meaningful differences between the surgeons [14]. Lack of understanding of reported data has been hypothesized to be one reason why public reporting initiatives in and of themselves may not necessarily translate into improvements in overall outcomes (eg, through steering patients toward highperforming centers) in fields where reporting efforts have been in been in place for longer periods of time [15,16].…”
Section: For Related Articles See Pages 211 220 and 342mentioning
confidence: 99%
“…Work by other groups highlights the potential unintended consequences of presenting information in a way that is not understandable. For example, a recent survey of adults presented with cancer surgery outcome data displayed in a fashion typical of outcome reports (designed without patient input) demonstrated that almost half of those surveyed said they would switch surgeons, when the data did not in fact show any clinically or statistically meaningful differences between the surgeons [14]. Lack of understanding of reported data has been hypothesized to be one reason why public reporting initiatives in and of themselves may not necessarily translate into improvements in overall outcomes (eg, through steering patients toward highperforming centers) in fields where reporting efforts have been in been in place for longer periods of time [15,16].…”
Section: For Related Articles See Pages 211 220 and 342mentioning
confidence: 99%